The possibility of critique in an era ruled by the media - Vuksanović, Divna; Ćalović, Dragan (2020)
Taking the philosophy of media as a starting point, this text examines the possibilities, forms and status of critique in our times which are dominated, at least in the West, by what is known as media culture. On the one hand, the text avoids reducing systemic and strategic critique of capitalism to merely a critical point of view, while on the other it problematizes and examines the critique of modern media practices. The authors implicitly conclude that merely asking these questions paves the road to comprehensive critical action, within the existing systems of this media universe, as well as beyond it, i.e. in the particular socio-economic system of thought and action. This text also examines the possibility of achieving critical practices through art, and in the context of emerging new technologies. Possibilities for critique within the framework of new media art are explored in particular, as this might revolutionize not only media practices, but also the social, historical and economical practices of capitalism as such.
U članku se, sa stanovišta filozofije medija, otvara pitanje o potencijalima, načinima i položaju kritike u našem dobu koje karakteriše, bar kada je reč o zapadnim kulturnim krugovima, dominacija tzv. medijske kulture. S jedne strane, izbegava se redukcija sistemske i strateške kritike sveta kapitala na puko kritičko mišljenje, dok se, s druge strane, problemski preispituje kritika delujuća unutar savremenih medijskih praksi. Autori implicitno zaključuju da je već samo otvaranje ovakvih pitanja utiranje puta za sveobuhvatno kritičko delovanje, kako unutar zatečenih sistema medijskog univerzuma, tako i izvan njega, odnosno u konkretnom društveno-ekonomskom sistemu mišljenja i delovanja. Takođe, u tekstu se razmatra mogućnost kritičkih praksi posredstvom umetnosti, odnosno unutar konteksta dejstva novih tehnologija. U tom smislu, posebno se istražuju potencijali za kritiku u okvirima novomedijske umetnosti, što bi trebalo da predstavlja uvod u revolucionisanje ne samo medijske, već i društveno-povesno-ekonomske prakse u eri kapitalizma.
Bibliografske bilješke uz tekst ; bibliografija: 10 jed.
Summary ; Sažetak.
Keywords: Kritika -- Mediji -- Kapitalizam -- Filozofija medija -- Novomedijska umjetnost